Critical influence of alumina content on the low temperature degradation of 2–3 mol% yttria-stabilized TZP for dental restorations. Issue 2 (February 2015) - Zhang, F.; Vanmeensel, K.; Inokoshi, M.; Batuk, M.; Hadermann, J.; Van Meerbeek, B.; Naert, I.; Vleugels, J.
Abstract The influence of 0.25, 2 and 5 wt.% alumina addition on the mechanical properties and low temperature degradation (LTD) of 3, 2.5 and 2 mol% yttria-stabilized TZP ceramics was investigated. The amount of alumina addition was observed to have a crucial impact on the degradation of Y-TZP ceramics. Independent on the yttria stabilizer content, 0.25 wt.% alumina had a higher degradation retarding effect to Y-TZP ceramics than 2 and 5 wt.% of alumina addition, which had a comparable effect. The apparent activation energy for the degradation process was increased by adding alumina, but it was the same for 0.25–5 wt.% alumina doped 3Y-TZP ceramics. For Y-TZPs containing a small amount of alumina addition, only the segregated Al3+ at the grain boundaries of the zirconia grains was effective to retard the degradation of Y-TZPs. The secondary phase Al2O3 grains increased the degradation kinetics, which might be attributed to the residual stresses.